Association between serum erythropoietin levels and renal reversibility in patients with renal impairment from multiple myeloma. (20th April 2020) - Kobayashi, Hiroki; Terao, Toshiki; Tsushima, Takafumi; Abe, Yoshiaki; Miura, Daisuke; Narita, Kentaro; Kitadate, Akihiro; Takeuchi, Masami; Matsue, Kosei
Abstract: Renal impairment (RI) is a common clinical presentation in patients with multiple myeloma (MM). Despite treatment with novel agents or management strategies that focus on the disease response, some patients develop irreversible RI. This study aimed to determine the influencing, clinical variables of renal reversibility in patients with RI treated with novel drugs. We analyzed 244 patients newly diagnosed with MM retrospectively. Maximum renal response was assessed according to the criteria for the definition of renal response proposed by the International Myeloma Working Group. Major renal response was defined as the occurrence of complete renal response or partial renal response. RI (a glomerular filtration rate < 50 mL/min/1.73 m 2 ) was observed in 110 patients (45%). In total, 56 patients (51%) achieved a major renal response. Serum erythropoietin (EPO) levels >25 mIU/mL ( P < .001) and a percentage of urinary albumin excretion ≤25% ( P < .001) were both significant factors that influenced the occurrence of major renal responses. Both remained significant factors associated with renal reversibility in the multivariate analysis. Patients were assigned a score of 1 each for EPO >25 mIU/mL and urinary albumin ≤25%. The estimated 6‐month rates of major renal responses of patients with scores of 2, 1, and 0 were 78.6%, 30.6%, and 0%, respectively ( P < .001). In conclusion, a serum EPO level >25 mIU/mL is an independent predictive factor for major renal response and may predict renal reversibility more accurately when urinary albumin level is congruently ≤25%. Abstract : Renal impairment (RI) is a common complication of multiple myeloma (MM), and this study aimed to determine the influencing, clinical variables of renal recovery in RI patients treated with novel drugs. Serum erythropoietin (EPO) levels >25 mIU/mL and percentage of urinary albumin ≤25%, were both significantly associated with a shorter time to major renal response. Serum EPO level >25 mIU/mL is an independent positive predictive factor for major renal response and predict renal reversibility more accurately when urinary albumin level is congruently ≤25%.